Sociocultural Behavior, Sex-Biased Admixture, and Effective Population Sizes in Central African Pygmies and Non-Pygmies - Paul Verdu; Noémie S. Becker; Alain Froment; Myriam Georges; Viola Grugni; Lluís Quintana‐Murci; Jean-Marie Hombert; Lolke van der Veen; Sylvie Le Bomin; Serge Bahuchet; Évelyne Heyer; Frédéric Austerlitz (2013)
Sociocultural phenomena, such as exogamy or phylopatry, can largely determine human sex-specific demography. In Central Africa, diverging patterns of sex-specific genetic variation have been observed between mobile hunter–gatherer Pygmies and sedentary agricultural non-Pygmies. However, their sex-specific demography remains largely unknown. Using population genetics and approximate Bayesian computation approaches, we inferred male and female effective population sizes, sex-specific migration, and admixture rates in 23 Central African Pygmy and non-Pygmy populations, genotyped for autosomal, X-linked, Y-linked, and mitochondrial markers. We found much larger effective population sizes and migration rates among non-Pygmy populations than among Pygmies, in agreement with the recent expansions and migrations of non-Pygmies and, conversely, the isolation and stationary demography of Pygmy groups. We found larger effective sizes and migration rates for males than for females for Pygmies, and vice versa for non-Pygmies. Thus, although most Pygmy populations have patrilocal customs, their sex-specific genetic patterns resemble those of matrilocal populations. In fact, our results are consistent with a lower prevalence of polygyny and patrilocality in Pygmies compared with non-Pygmies and a potential female transmission of reproductive success in Pygmies. Finally, Pygmy populations showed variable admixture levels with the non-Pygmies, with often much larger introgression from male than from female lineages. Social discrimination against Pygmies triggering complex movements of spouses in intermarriages can explain these male-biased admixture patterns in a patrilocal context. We show how gender-related sociocultural phenomena can determine highly variable sex-specific demography among populations, and how population genetic approaches contrasting chromosomal types allow inferring detailed human sex-specific demographic history.